Police-Obtained Evidence and the Constitution: Distinguishing Unconstitutionally Obtained Evidence from Unconstitutionally Used Evidence - Loewy, Arnold H. (1989)
The article will consider four different types of police-obtained evidence: evidence obtained from an unconstitutional search and seizure, evidence obtained from a Miranda violation, confessions and lineup identifications obtained in violation of the sixth amendment right to counsel, and coerced confessions. My conclusions are that evidence obtained from an unconstitutional search and seizure is excluded because of the police misconduct by which it was obtained. On the other hand, evidence obtained from a Miranda violation is (or ought to be) excluded because use of that evidence compromises the defendant's procedural right not to be compelled to be a witness against himself. Confessions and lineup identifications obtained after the right to counsel has attached also are excluded for procedural reasons. Finally, all coerced confessions are excluded because procedurally their introduction violates the fifth amendment. Some coerced confessions are also excluded because of police misconduct in obtaining them. Ultimately, this article demonstrates that whether evidence is unconstitutionally obtained or unconstitutionally used ought to make a difference, and that the Court's frequent failure to think in these terms has caused it to overlook the differences